2022
DOI: 10.1002/hsr2.657
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: COVID‐19 mortality and its predictors in the elderly: A systematic review

Abstract: Background and Aims: Older people have higher rates of comorbidities and may experience more severe inflammatory responses; therefore, are at higher risk of death. Herein, we aimed to systematically review the mortality in coronavirus disease 2019 (COVID-19) patients and its predictors in this age group.Methods: We searched PubMed, Web of Science, and Science Direct using relevant keywords. Retrieved records underwent a two-step screening process consisting of title/abstract and full-text screenings to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
79
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 67 publications
(193 reference statements)
13
79
0
6
Order By: Relevance
“…In this study, as widely demonstrated in the literature, older age, the presence of at least one comorbidity, and male sex were confirmed as risk factors associated with increased COVID-19 mortality [ 12 , 13 ]. In our cohort, among the collected comorbidities, cardiovascular, cerebrovascular, chronic pulmonary, renal, and hematologic diseases and solid organ tumors were significantly associated with increased mortality.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, as widely demonstrated in the literature, older age, the presence of at least one comorbidity, and male sex were confirmed as risk factors associated with increased COVID-19 mortality [ 12 , 13 ]. In our cohort, among the collected comorbidities, cardiovascular, cerebrovascular, chronic pulmonary, renal, and hematologic diseases and solid organ tumors were significantly associated with increased mortality.…”
Section: Discussionsupporting
confidence: 79%
“…In the largest cohort of hospitalized patients with COVID-19, the increased age was an independent risk factor for mortality, with odds risk approximately doubling for an age between 65 and 79 years compared to 50 and 64 years [ 19 ]. A systematic review showed that mortality from COVID-19 was independently associated with the patient’s age and older patients were more likely to be admitted to intensive care and develop ARDS [ 20 ]. Patients aged 70 years represented up to 28 of the total COVID-19 critically ill patients admitted to intensive care [ 21 ].…”
mentioning
confidence: 99%
“…Aging increases inflammatory responses to pathogens and reduces the efficacy of suppressing infections. A positive correlation was confirmed between older ages and increased mortality rates (MR); sixty-year-old patients had mortality rates of 4.5% vs 1.4% for patients under sixty years[ 3 , 4 ]. Recinella et al [ 5 ] study declared a one-and-a-half-fold increase in MR for every five years of a patient's age.…”
Section: To the Editormentioning
confidence: 99%